Comparing the performance of players unknown battle ground (PUBG) mobile app on iphone x and samsung s9 plus smartphones - Mkpojiogu E.O.C.; Sherriff G.; Hussain A.; Hashim W. (Science and Engineering Research Support Society, 2023)
In this paper, we present the results of a comparative evaluation of the performance of the Players Unknown Battleground (PUBG) Mobile app on iPhone X and Samsung S9 Plus smartphones. The outcome indicates that Samsung S9 Plus performed better than iPhone X as perceived by players of the PUBG mobile game. This finding suggests that the quality of iPhone X for PUBG mobile app play should be enhanced toimprove on the experience of its users. 2020 SERSC.